Wireless Online Atmospheric Electric Field Measurement System Based on Rotating-vane Electric Field Mill - Muhammad Abu Bakar Sidik; Hamizah Shahroom; Zolkafle Buntat; Yanuar Zulardiansyah Arief; Zainuddin Nawawi; Muhammad ‘Irfan Jambak (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
One of the popular methods to measure atmospheric quasi-static electric field is by using rotating-vane electric field mill (REFM) sensor. By observing electric fields strength in atmosphere, occasion of lightning incident can be forecasted. This paper proposes an integration of REFM with an online wireless data monitoring system for long distance observation and data collection. This method reduces system costs by removing the computer and data logger on-site. Furthermore, it reduces the required man-hour to gather data from the REFM. The development includes hardware and software design in order to improve efficiency the atmospheric electric field measurement system. The contribution of this paper is the design of the electronic circuit which converts the ac signal from the REFM sensor to dc signal and then correlates the signal to the electric field strength in the vicinity. Subsequently the information is transmitted via a wireless data transmission system, using the Global System Mobile Communication (GSM) network. Using the proposed method, all the data from sensors can be observed and analyse immediately from any location.